2022
DOI: 10.1002/glia.24270
|View full text |Cite
|
Sign up to set email alerts
|

Pten associates with important gene regulatory network to fine‐tune Müller glia‐mediated zebrafish retina regeneration

Abstract: Unlike mammals, zebrafish possess a remarkable ability to regenerate damaged retina after an acute injury. Retina regeneration in zebrafish involves the induction of Müller glia-derived progenitor cells (MGPCs) exhibiting stem cell-like characteristics, which are capable of restoring all retinal cell-types. The induction of MGPC through Müller gliareprograming involves several cellular, genetic and biochemical events soon after a retinal injury. Despite the knowledge on the importance of Phosphatase and tensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 127 publications
(221 reference statements)
0
3
0
Order By: Relevance
“… 37 , 92 In addition, Gupta and his colleagues have reported that downregulation of Pten activates Akt and enhances MGPCs proliferation in zebrafish. 93 Gao and his colleagues have reviewed the current knowledge regarding the roles of Wnt/β-Catenin and Hedgehog Pathway in RMGC reprogramming. 36 , 94 , 95 …”
Section: Regulators Mediating the Dedifferentiation And Proliferation...mentioning
confidence: 99%
“… 37 , 92 In addition, Gupta and his colleagues have reported that downregulation of Pten activates Akt and enhances MGPCs proliferation in zebrafish. 93 Gao and his colleagues have reviewed the current knowledge regarding the roles of Wnt/β-Catenin and Hedgehog Pathway in RMGC reprogramming. 36 , 94 , 95 …”
Section: Regulators Mediating the Dedifferentiation And Proliferation...mentioning
confidence: 99%
“…However, use of these tools in adult zebrafish is more difficult. Many morpholinos used to target genes in adult retina have been designed with a positively charged lissamine fluorescent molecule as a 3′ end modification ( Craig et al, 2010 ; Thummel et al, 2010 , 2011 ; Gupta et al, 2023 ), and require electroporation after injection of the morpholino for successful penetrance into cells. Many zebrafish labs do not have an electroporation device readily available, which cost from US $16,000 to $19,000 in 2021, and must rely on alternative strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the remarkable regenerative capacity of zebrafish, many studies have used this model to uncover the molecular underpinnings of retinal regeneration. Furthermore, a variety of signaling pathways, epigenomic remodeling factors, and immune response components have been identified to be required for Müller glia reprogramming and/or proliferation (e.g., Boyd et al, 2023; Campbell et al, 2021; Conner et al, 2014; Elsaeidi et al, 2018; Fausett et al, 2008; Gupta et al, 2023; Hamon et al, 2016; Kara et al, 2019; Kaur et al, 2018; Lee et al, 2020; Lenkowski et al, 2013; Lourenço et al, 2021; Mitchell et al, 2018; Mitra et al, 2022; Nagashima et al, 2020; Nelson et al, 2012, 2013; Powell et al, 2012, 2013; Rajaram et al, 2014; Ramachandran et al, 2010, 2011; 2012; Sahu et al, 2021; Sharma et al, 2019; Sifuentes et al, 2016; Silva et al, 2020; Song et al, 2023; White et al, 2017; Zhao et al, 2014). Despite these advances, we know little about the transcriptional regulation of pro‐regenerative genes or the genomic and epigenetic landscapes affecting their expression during the injury and regenerative responses.…”
Section: Introductionmentioning
confidence: 99%